Pengaruh Kebiasaan Belajar Dan Kreativitas Belajar Terhadap Prestasi Belajar Siswa SMP Negeri 2 Siantar - Joel Simanjuntak; Anggun Tiur Ida Sinaga; Tumpal Manahara Siahaan (JOURNAL SAINS STUDENT RESEARCH, 2023)
This research aims to determine the influence of study habits and learning creativity on learning achievement at SMP Negeri 2 Siantar. The type of research used in this research is quantitative research with research using survey methods. The population in this study was all 245 students in class VIII of SMP Negeri 2 Siantar. The sample in this study was 152 students. The sampling technique uses a random sampling technique where sampling and population are taken randomly. Data collection techniques use questionnaires. The data in this study were analyzed using the normality test, linearity test, multicollinearity test, heteroscedasticity test, multiple regression analysis, t test, F test, and coefficient of determination test. The results of the research show that there is an influence of habit on students' social studies learning achievement with tcount 2.021 > 1.976 ttable. Furthermore, there is an influence of learning creativity on students' social studies learning achievement with tcount > ttable (11.844>1.976). and there is an influence between study habits and learning creativity on students' social studies learning achievement with Fcount > Ftable (12,684>3,056).